DETERMINANT FACTORS OF HYPERTENSION IN THE ELDERLY AT PUBLIC HEALTH CENTER IN PALEMBANG, SOUTH SUMATERA INDONESIA - Azwaldi, Azwaldi; Maksuk, Maksuk; Putri Maharani; Intan Kumalasari (Perhimpunan Ahli Epidemiologi Indonesia, 2023)
ABSTRACT Background: Hypertension is one of Indonesia's highest causes of death and is known as the silent killer. Several risk factors for hypertension include age, gender, heredity, and lifestyle. This study aimed to analyze the determinants of hypertension in the elderly in the work area of the Palembang City Health Center.. Methods: This research is an analytical observational study with a cross-sectional design. This research was conducted from March to May 2021 in the working area of the Padang Selasa Health Center, Palembang City. Samples were taken randomly, with the number of samples as many as 106 respondents. Data were collected by interview using a questionnaire and data analysis using the chi-square test and multiple logistic regression. Results: Bivariate analysis showed that the variables statistically significantly related to hypertension in the elderly were heredity history and the incidence of stress with p<0.05. Meanwhile, the results of multivariate analysis showed that heredity (OR=0.089; p=0.0005; 95% CI= 0.033-0.239) was the most dominant factor in the incidence of hypertension in the elderly in the Padang Selasa Palembang Public Health Center working area in 2021. The elderly with a history of heredity have a risk 12 times riskier than those without a history of heredity. Conclusion: The majority of the elderly found with hypertension are female. The determinants of hypertension in the elderly are heredity and stress, and the most dominant factor causing hypertension in the elderly is a history of hereditary hypertension.